Implementasi Kuliah Kerja Lapangan Prodi Aqidah dan Filsafat Islam dalam Pengembangan Literasi Wisata Spiritual Sulawesi Selatan: The Implementation of Field Work in the Aqidah and Islamic Philosophy Study Program in the Development of Spiritual Tourism Literacy in South Sulawesi - Askaryna, Andini; Malliongi, M. Takbir; Rahmawati, Rahmawati; Hanis Gani, Nur Azizah Putri; Anggreni, Ferlita; Alifiah, Kanaya Iffah; Ilyas, M.Akbar; Ridwan, Muh; Tajering, Tajering; Almaudhudhy, A. Muh. Ilham Noer; Paleppangi, Muh. Albadri (PADAIDI: Journal of Tourism Dedication, 2024)
This study examines the roles of three key figures in the spread of Islam in South Sulawesi, namely Datuk Ri Bandang, Datuk Ri Panggentungan, and Syekh Yusuf, as well as the perspectives of pilgrims and tomb guardians in preserving historical and spiritual values. These figures significantly contributed to the Islamization of South Sulawesi, bringing substantial changes to the social and cultural structures of the local communities. The motivations of pilgrims visiting these tombs include respect for historical values, spiritual beliefs, and seeking blessings. Tomb guardians play a crucial role not only in maintaining the physical condition of the tombs but also in safeguarding Islamic teachings in alignment with local values. This study highlights the importance of preserving these historical sites as cultural heritage and religious tourism destinations, as well as the need to educate the public about proper pilgrimage practices according to Islamic teachings. The findings of this study contribute to the efforts of preserving spiritual values and developing culture-based tourism in South Sulawesi.